Effects of 3-Methyladenine on Microglia Autophagy and Neuronal Apoptosis After Radiation-Induced Brain Injury. Issue 2 (20th May 2022) - Feng, Huichao; Cui, Yahuan; Liu, Jing; Liu, Meiyi; Zhou, Wei; Yan, Zhenyu; Zhang, Haixia; Wang, Yingman; Wang, Xueming; Liu, Xiaomin; Chen, Naiyao
Objective: To determine the effect of the autophagy inhibitor, 3-methyladenine (3-MA), on cognitive function changes, microglia activity, neuronal apoptosis, and inflammation in rats following radiation-induced brain injury. Methods: The following groups were established: control, model, and 3-MA. A rat model of radiation-induced brain injury was generated with a medium dose of X-rays. A Morris water maze was used to observe the cognitive function of the rats. H&E staining was used to observe the pathological changes in the hippocampus. The morphological and quantitative changes of neuronal nuclear (NeuN)-positive neurons and Iba-1-positive microglia in the ipsilateral hippocampus were analyzed by immunohistochemistry. Western blot analysis was done to measure the changes of NeuN ionized calcium binding adapter molecule 1(Iba-1) and apoptosis-related proteins. Immunofluorescence staining of Iba-1 and Microtuble-associated protein light chain 3 (LC3) was done to evaluate the changes in microglia autophagy. TUNEL staining was used to detect apoptosis in the hippocampus. Enzyme-Linked Immunosorbent Assay was used to detect the levels of TNF-α and IL-6 as a measure of the inflammatory response in the hippocampus. Results: After irradiation, the nucleus of the neurons in the hippocampus was constricted, the pyramidal tract structure was disordered, neuronal apoptosis was increased ( P < .001), the expression of microglia increased ( P < .01), autophagy was increased ( P < .05), and conversion of microglia to the M2 type increased ( P < .05). After 3-MA administration, the level of autophagy decreased ( P < .05), the damage to the hippocampal region was reduced, neuronal apoptosis decreased ( P < .01), and the activity of the microglia decreased ( P < .01). Conclusion: Radiation can active the Microglia. 3-MA inhibits autophagy and excessive activity in microglia, and promotes the conversion of microglia from the M1 to the M2 type, thereby promoting the recovery of brain tissue following radiation exposure.